2017
DOI: 10.18001/trs.3.2(suppl1).9
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with a Sales Policy on Flavored Non-cigarette Tobacco Products

Abstract: Objectives: We assessed the effect of the New York City (NYC) policy restricting sales of flavored non-cigarette tobacco products on retail sales using a quasi-experimental comparison design. We also studied possible cross-border purchasing and product substitution by consumers. Methods: We compiled retail scanner data for January 2010–January 2014 for NYC, a proximal comparison area (PCA) surrounding NYC, and the US. We used regression models to assess trends in sales of flavored cigars, smokeless tobacco (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…These results are consistent with findings from recent studies evaluating the impact of similar flavoured product restriction policies implemented in NYC and two cities in Minnesota 10 11. A notable strength of the present study is that it expands on sampling used in these studies to include a state-wide sample of retailers of all types and sizes, which for Q1–Q4 comprises a full sample of all retailers in the study communities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with findings from recent studies evaluating the impact of similar flavoured product restriction policies implemented in NYC and two cities in Minnesota 10 11. A notable strength of the present study is that it expands on sampling used in these studies to include a state-wide sample of retailers of all types and sizes, which for Q1–Q4 comprises a full sample of all retailers in the study communities.…”
Section: Discussionsupporting
confidence: 88%
“…As of December 2018, 138 municipalities in Massachusetts, including Boston, have passed a flavoured restriction policy, covering 61% of the state’s total population 8. Policy evaluation studies conducted in NYC and in Minneapolis and St. Paul have shown reductions in sales of non-cigarette flavoured tobacco products in large retailers, pharmacies, grocery and convenience stores following policy implementation 9–11. However, it is not yet known whether these results extend to other localities or all types of retailers.…”
Section: Introductionmentioning
confidence: 99%
“…These are summarized in Additional file 1: Table 1. Of the nine excluded studies, one study found that adolescents had a 37% lower odds of ever trying flavored tobacco products and a 28% lower odds of ever using tobacco products post ban [54], two studies found that sales of other tobacco products fell [55,56], and six considered compliance [57][58][59][60][61][62]. The studies of compliance indicated mixed levels of compliance, with flavor products still available in up to 50% of retailers that were not allowed to sell flavored tobacco and smaller stores often continuing to carry banned products with staff oblivious to the ban [58,[60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations of non-menthol flavoured tobacco sales restrictions have found that these types of policies can be effective in reducing the availability of flavoured tobacco products. [15][16][17] However, because menthol has often been excluded from sales restrictions, there is a paucity of published literature about the impact of menthol tobacco sales restrictions on the retail environment. We are only aware of one published study to date that examined the impact of a menthol tobacco restriction on the retail environment.…”
Section: Introductionmentioning
confidence: 99%